Understanding Student Needs for Effective Online English Grammar Learning: A Quantitative Descriptive Study - Permatasari, Sinta Dewi; Sunardi; Sumaryati, Sri (VELES Voices of English Language Education Society, 2024)
With the growing need for accessible English learning in online education, this study explores students' requirements for mastering English grammar in a virtual environment at the educational startup "Scholars" in Surakarta, Indonesia. The study aimed to identify students' learning needs and challenges in online grammar classes to provide recommendations for more effective instructional support. Using a quantitative descriptive approach, data were collected from 38 students through questionnaires and proficiency tests, focusing on their perceptions and performance in online English grammar learning. The findings showed that over 50% of students strongly needed structured, accessible digital materials, such as interactive e-books or guidebooks, to facilitate independent grammar study. Students struggled to identify word forms and understand sentence structures, contributing to low proficiency rates, as evidenced by a 40% failure to meet the passing grade. The research highlights that current materials, limited to PowerPoint presentations and PDF files, are insufficient to meet students' learning needs. The study concludes that integrating digital, interactive learning resources with exercises and structured materials could better support students' autonomy, improve engagement, and address learning gaps in online English grammar instruction. This approach promises to enhance learning outcomes and motivation in virtual English education.